Co‐Doping Approach for Enhanced Electron Extraction to TiO2 for Stable Inorganic Perovskite Solar Cells - Thomas W. Gries; Davide Regaldo; Hans Köbler; Noor Titan Putri Hartono; Steven P. Harvey; Maxim Simmonds; Chiara Frasca; Marlene Härtel; Gennaro V. Sannino; Roberto Félix; Elif Hüsam; Ahmed Saleh; et al. (Small Science, 2025)
Inorganic perovskite CsPbI3 solar cells hold great potential for improving the operational stability of perovskite photovoltaics. However, electron extraction is limited by the low conductivity of TiO2, representing a bottleneck for achieving stable performance. In this study, a co‐doping strategy for TiO2 using Nb(V) and Sn(IV), which reduces the material's work function by 80 meV compared to Nb(V) mono‐doped TiO2, is introduced. To gain fundamental understanding of the processes at the interfaces between the perovskite and charge‐selective layer, transient surface photovoltage measurements are applied, revealing the beneficial effect of the energetic and structural modification on electron extraction across the CsPbI3/TiO2 interface. Using 2D drift‐diffusion simulations, it is found that co‐doping reduces the interface hole recombination velocity by two orders of magnitude, increasing the concentration of extracted electrons by 20%. When integrated into n–i–p solar cells, co‐doped TiO2 enhances the projected TS80 lifetimes under continuous AM1.5G illumination by a factor of 25 compared to mono‐doped TiO2. This study provides fundamental insights into interfacial charge extraction and its correlation with operational stability of perovskite solar cells, offering potential applications for other charge‐selective contacts.